2016
DOI: 10.5455/medarh.2016.70.457-459
|View full text |Cite
|
Sign up to set email alerts
|

Opiate Analgesia Treatment Reduced Early Inflammatory Response After Severe Chest Injuries

Abstract: Background:The frequency of severe chest injuries are increased. Their high morbidity is followed by systemic inflammatory response. The efficacy of pharmacological blockade of the response could prevent complications after chest injures.Aim:The aim of the study was to show an inflammatory response level, its prognostic significant and length of hospital stay after chest injures opiate analgesia treatment.Methods:Sixty patients from Department of Thoracic Surgery with severe chest injures were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Moreover, using the correct pain relief methods, it is aimed to remove secretions easily, increase compliance with respiratory physiotherapy, provide early mobilization, reduce the incidence of complications, increase the quality of life, reduce the occurrence of chronic pain syndrome, accelerate the discharge process and thus reduce the cost. 15 In our study, the use of CCO significantly reduced the level of pain and the rate of atelectasis. Although no statistical difference was found between the two groups in the length of hospital stay in our study, Mészáros et al 17 reported that the use of chest orthosis could significantly reduce the length of hospital stay in patients with rib fractures.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, using the correct pain relief methods, it is aimed to remove secretions easily, increase compliance with respiratory physiotherapy, provide early mobilization, reduce the incidence of complications, increase the quality of life, reduce the occurrence of chronic pain syndrome, accelerate the discharge process and thus reduce the cost. 15 In our study, the use of CCO significantly reduced the level of pain and the rate of atelectasis. Although no statistical difference was found between the two groups in the length of hospital stay in our study, Mészáros et al 17 reported that the use of chest orthosis could significantly reduce the length of hospital stay in patients with rib fractures.…”
Section: Discussionsupporting
confidence: 54%
“…In 2017, the Chest Wall Injury Society published a consensus statement regarding the overall management of patients with rib fractures, emphasizing an organised respiratory physiotherapy 15 . The guideline supported by the Association for the Surgery of Trauma recommends a multimodal approach instead of epidural analgesia or opioids alone in patients with rib fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation